2002
DOI: 10.1021/bi015863z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Contact Region between the Tridecapeptide α-Factor Mating Pheromone ofSaccharomyces cerevisiaeand Its G Protein-Coupled Receptor by Photoaffinity Labeling

Abstract: Saccharomyces cerevisiae haploid cells communicate with their opposite mating type through peptide pheromones (alpha-factor and a-factor) that activate G protein-coupled receptors (GPCRs). S. cerevisiaewas used as a model system for the study of peptide-responsive GPCRs. Here, we detail the synthesis and characterization of a number of alpha-factor (Trp-His-Trp-Leu-Gln-Leu-Lys-Pro-Gly-Gln-Pro-Met-Tyr) pheromone analogues containing the photo-cross-linkable group 4-benzoyl-L-phenylalanine (Bpa). Following chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 31 publications
5
57
0
Order By: Relevance
“…16,17 Among the many synthetic β-turn peptidomimetics restricted by cyclization, (R)-γ-lactam conformational constraint incorporating [3-(R)-amino-2-oxo-1-pyrrolidineacetamido] in place of ProGly at residues 8 and 9 was reported to have the best activity only equal to that of parent peptide, [Nle ing approach involving the photoactivatable groups attached to the α-factor backbone was developed. 28,30,44,[51][52][53]55,56 pBenzoyl-L-phenylalanine (Bpa) and 3,4-Dihydroxyphenylalanine (DOPA) was reported to have a desirable property for this purpose, although incorporation of these groups at various positions in α-factor have been shown to result in a less than 30-fold decrease in receptor affinity. 44,51,55 Biotin (Bio) tagging modification of DOPA analog (Bio 7…”
Section: 16mentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Among the many synthetic β-turn peptidomimetics restricted by cyclization, (R)-γ-lactam conformational constraint incorporating [3-(R)-amino-2-oxo-1-pyrrolidineacetamido] in place of ProGly at residues 8 and 9 was reported to have the best activity only equal to that of parent peptide, [Nle ing approach involving the photoactivatable groups attached to the α-factor backbone was developed. 28,30,44,[51][52][53]55,56 pBenzoyl-L-phenylalanine (Bpa) and 3,4-Dihydroxyphenylalanine (DOPA) was reported to have a desirable property for this purpose, although incorporation of these groups at various positions in α-factor have been shown to result in a less than 30-fold decrease in receptor affinity. 44,51,55 Biotin (Bio) tagging modification of DOPA analog (Bio 7…”
Section: 16mentioning
confidence: 99%
“…28,30,44,[51][52][53]55,56 pBenzoyl-L-phenylalanine (Bpa) and 3,4-Dihydroxyphenylalanine (DOPA) was reported to have a desirable property for this purpose, although incorporation of these groups at various positions in α-factor have been shown to result in a less than 30-fold decrease in receptor affinity. 44,51,55 Biotin (Bio) tagging modification of DOPA analog (Bio 7…”
Section: 16mentioning
confidence: 99%
See 1 more Smart Citation
“…As with other GPCR proteins and in keeping with the crystal structure of rhodopsin (31), there are seven TM domains, and the third TM domain appears unusually long. The N terminus is predicted to be extracellular, and the intracellular loops TM3-4 and TM5-6 are thought to form a cleft in which the cognate G protein ␣-subunit binds (32)(33)(34). There is a clear relationship between codon diversity and TM topology of SRZ proteins.…”
Section: Positive Selection In the Sr Superfamilymentioning
confidence: 99%
“…Coupling energies found for two directly interacting residues can be converted to a distance constraint and in this respect are similar in nature to nuclear Overhauser connectivities (11). Thus, detailed knowledge of coupling energies for a ligand and a receptor can be used to dock the ligand into a receptor whose structure is available (12-14).We have been studying the biology of a yeast mating factor GPCR, Ste2p, and its contacts with α-factor [Trp 1 -His-Trp-Leu-Gln-Leu-Lys-Pro-Gly-Gln-Pro-Met-Tyr 13 ], the tridecapeptide ligand of this GPCR, by employing α-factor analogs, site-specific mutagenesis and photocrosslinking analysis (15)(16)(17)(18). These studies together with extensive molecular biology investigations (19-23) have indicated likely interactions between Y266 and residues near the amine terminus of α-factor.…”
mentioning
confidence: 99%